Desenvolvimento de uma metodologia eletroanalítica para determinação de agentes sulfitantes no vinho - Lozer, Tais Cazzotti (2022)
Sulfite agents are the most commonly used compounds in foods and beverages to prevent oxidation and inhibit the growth of bacteria. Despite the advantages of using these sulfite agents, their concentration must be controlled, because these agents can affect the quality and cause health issues. This additive is intentionally added to the wine to prevent its oxidation. In Brazil, the Brazilian Health Regulatory Agency (ANVISA) monitors this additive and establishes a maximum value of 0.35 g L−1 of SO2 in the beverage. Electrochemical techniques, such as voltammetry, have potential applications in sulfite determination in beverages. The main advantages of these techniques include simplicity, high sensitivity, and compatibility with colored samples, which minimizes sample pretreatment requirements. Therefore, this study describes the development of an electroanalytical methodology using square wave voltammetry (SWV) and a portable system to quantify sulfite agents in wine samples. SWV parameters were optimized using the design of experiments in 0.1 mol L−1 phosphate buffer (pH 4.0) as supporting electrolyte and commercials screen-printed carbon electrodes (SPCEs) modified with carboxyl functionalized multi-walled carbon nanotubes (MWCNT-COOH). The square wave voltammogram presented two oxidation peaks, one around 0.5 V and the other around 0.7 V that shifted to more positive potentials, with increasing analyte concentration. Nonetheless, we chose the oxidation peak with a potential around 0.7 V, which corresponds to HSO3−. For that potential we obtained values of the limit of quantitation and detection of 39.24 × 10−5 and 12.95 × 10−5 mol L−1 were obtained, respectively, in the linear range of 5.0 × 10−6 to 6.0 × 10−3 mol L−1, presenting an R2 equal to 0.997. To evaluated the selectivity, the method developed did not show significant interference between possible interferents in wine samples with the variation of 4.00 to −7.00%. Furthermore, reals samples of wines were analyzed by the proposed methodology and compared with the official method (iodometric titration), and to values of sulfite concentration were not presented as statistically different (Test F: pvalue > 0.05). These results reinforce the possibility of applying the proposed method in loco in practical and fast way, without the need to use significant amounts the samples.